TVRI Yogyakarta in the era of disruption: Maintaining the existence of cultural wisdom through the broadcast of "Canthing - Nurrohmah, Shinta; Rifa'i, Akhmad (Islamic Communication Journal, 2023)
The existence of social media, which intensively displays similarities with television shows, has resulted in the decline of the television industry. Thus shifting the tastes of the younger generation by offering modern trends rather than local culture. This also happened on local Republic of Indonesia television, such as TVRI Yogyakarta. This article aims to reveal TVRI Yogyakarta's strategy for maintaining cultural wisdom through the Canthing program amid an era of media disruption. Data was obtained through observation, interviews, and documentation related to research. The results of this research show that TVRI Yogyakarta's strategy in maintaining the existence of the Canthing program is through the use of professional human resources, packaging the program with the main content of Javanese culture, methods of approaching and involving the youth community and socializing the program through advertisements on various TVRI Yogyakarta programs. by using social media as a form of divergence, convergence, and cyclone methods. TVRI Yogyakarta tries to provide innovations in the programs presented according to current developments so that they continue to be in demand by the current generation and beyond. This study contributes to the development of theories and concepts of the function of media as a cultural medium, which is also the orientation of Islamic communication. ***Eksisnya media sosial yang gencar menampilkan kemiripan dengan tayangan televisi mengakibatkan menurunnya industri pertelevisian sehingga menggeser selera generasi muda dengan penawaran trend modern daripada budaya lokalnya. Hal tersebut juga terjadi di televisi lokal Republik Indonesia seperti TVRI Yogyakarta. Tulisan ini bertujuan untuk membongkar bagaimana strategi TVRI Yogyakarta dalam menjaga eksistensi kearifan budaya di tengah era disrupsi media melalui program Canthing. Data diperoleh melalui observasi, wawancara, dan dokumentasi yang terkait dengan penelitian. Hasil dari penelitian ini diperoleh bahwa strategi TVRI Yogyakarta dalam mempertahankan eksistensi program Canthing melalui penggunaan sumber daya manusia yang profesional, pengemasan program dengan mengusung konten utama budaya Jawa, metode pendekatan dengan melibatkan komunitas anak muda, dan sosialisasi program melalui iklan pada berbagai program acara TVRI Yogyakarta dengan pemanfaatan media social sebagai bentuk dari metode divergensi, konvergensi, dan siklon. TVRI Yogyakarta berusaha memberikan inovasi baru terhadap program-program yang disajikan sesuai perkembangan zaman sehingga terus diminati oleh generasi masa kini dan seterusnya. Studi ini berkontribusi bagi pengembangan teori dan konsep fungsi media sebagai sarana kebudayaan, yang juga menjadi orientasi dari komunikasi Islam.